Citizens' policy perception, policy measures, and trust in political institutions after the first wave of COVID-19 - Vincenzo Memoli (QOE-IJES, 2024)
Crises bring both human consequences and political repercussions. COVID-19, like any other crisis, strained both European governments and public support for them. During the first wave of the pandemic, political trust was correlated with public adherence to infection containment measures in the major democracies. At the end of the first wave, how did public perceptions of COVID-19 measures and of measures introduced by institutions to protect health and the economy affect the bond of political trust between the governed and the governors? Using Eurobarometer data, we estimate the effects on political trust of the public’s assessment of institutional performance, political output and policy. Applying various multilevel regression models, we show that, at the end of the first wave of the pandemic, political trust was positively affected by institutional performance and only partially affected public perceptions and the policy measures taken by governments to contain the spread of the virus.